EFFORTS TO IMPROVE DRIBBLING IN BASKETBALL GAMES THROUGH A SCIENTIFIC APPROACH WITH BALL MODIFICATIONS IN CLASS VI STUDENTS OF STATE ELEMENTARY SCHOOL 028066 BINJAI UTARA - Subono Subono; Imran Akhmad; M Irfan (Universitas Negeri Medan, 2021)
This research is a classroom action research (Classroom Action Research) with implementation stages including planning, implementation of the action, observation, and reflection. The location of this research was carried out in class VI sekolah dasar negeri 028066 binjai utara. After the data is collected, an analysis will be carried out: From the test of learning outcomes before using the scientific approach (pre-test) obtained 9 students (29.03%) who have achieved mastery learning, while 22 students (70.69%) have not reached the level of mastery learning. With an average value of 58.33. Then learning is carried out using a scientific approach in cycle I. From the test of learning outcomes in Cycle I dribbling through a scientific approach in cycle 1, 19 students (61.29%) have reached the level of mastery learning, while 12 students (38.70%) have not. achieve the level of mastery learning. With an average value of 69.73. Then the learning was carried out again dribbling with a scientific approach. From the learning outcomes test conducted in the second cycle, 27 students (87.09%) achieved the mastery level of learning, while 4 students (12.90%) had not yet reached the mastery level in learning, with an average score of 81.66. In this case, it can be seen that there is an increase in the average value of learning outcomes in cycle I and cycle II, namely 11.93. Based on the results of data analysis, it can be said that a scientific approach it can improve learning outcomes by dribbling a basketball for class VI sekolah dasar negeri 028066 binjai utara.Keywords: Improving, Learning Outcomes, Dribbling